Formally specifying and verifying mobile agents – model checking mobility: the MobiOZ approach. (2nd September 2008) - Taguchi, Kenji; Dong, Jin Song
The notion of the mobile agent has been around for over a decade in order to capture the new form of computation in communication networks. A mobile agent is a computing entity which can move around different hosts on the network, carrying its state and procedures. Mobile Object-Z (MobiOZ), which is designed to provide a practical means to the specifiers who are working on mobile agent applications, is an extended notation of Object-Z, with mobile and communication primitives for specifying and verifying mobile agent applications. In this paper, we will give an overview of the MobiOZ notation and present its semantic foundation, then demonstrate how the specifications in MobiOZ can be simulated and verified by SPIN, a model checker, by translating MobiOZ specifications into PROcess MEta LAnguage (PROMELA), a process-based formal specification language of SPIN.